Gabapentin acutely increases the apnea–hypopnea index in older men: data from a randomized, double‐blind, placebo‐controlled study. (24th January 2017) - Piovezan, Ronaldo D.; Kase, Camila; Moizinho, Renato; Tufik, Sergio; Poyares, Dalva
Summary: Although drugs with sedative properties may increase the risk of airway collapse during sleep, their acute effects on the apnea–hypopnea index in older adults are under‐reported. We investigated the acute effects of gabapentin (GABA) on sleep breathing in older men without sleep apnea. A double‐blind, randomized, placebo‐controlled cross‐over pilot study using a bedtime dose of gabapentin 300 mg was conducted in eight non‐obese older men. Polysomnography measured the effects of the intervention. The apnea–hypopnea index was higher in the gabapentin arm than in the placebo arm (22.4 ± 6.1 versus 12.2 ± 4.3, P  ≤ 0.05, d : 0.67), as was the oxygen desaturation index (20.6 ± 5.8 versus 10.8 ± 3.9, P  ≤ 0.05, d : 0.68). The number needed to harm was four. A subset analysis demonstrated that differences in sleep respiratory parameters were present only during non‐rapid eye movement sleep, as well as only in the supine position. No adverse events were reported. Hence, gabapentin worsened sleep breathing acutely compared with placebo. Long‐term clinical trials are warranted to elucidate the clinical relevance of these findings for the safety profile of GABAergic agents.